(untitled) (diségno, 2019)
As we perceive it today, the territor y is not always the organic result of natural and anthropic processes of change and transformation linked to the development of environmental, cultural, social, economic and political contexts. The contribution illustrates this assumption by critically reviewing the research experiences conducted in the field of Representation aimed at supporting better and more effective government actions and protection of material and immaterial systems concerned. The results of sur veys that have been the methodological foundation and essential cultural heritage for a series of research groups formed since 1974 in the then Institute of Technical Architecture of the Politecnico di Torino are recalled: occasions that required working on representations of different levels of detail, organized in an increasingly integrated system of information, where the vastness of the fields of investigation and approaches has anchored itself to the tradition of the cleverest Italian culture, finding, over time, that unprecedented support offered by information technologies that has allowed us to reach new scientific milestones.